Hans Jonas e a responsabilidade do homem frente ao desafio biotecnológico - Lilian Simone Godoy Fonseca (2009)
The main objective of this study was to examine the ethical formulation of the German philosopher, Hans Jonas, in light of the challenge put by the biotechnological progress destined to the application to the human beings not only with the goal to cure, but to improve or to cross the human race with other species, even machines. Something that becomes more and more possible, because of the increasing progress of the researches in this field. It was tried to show the aspects that are in question, mainly, in the proposition of called positive eugenics and in the post-human project, to confront them with the jonassian ethical formulation and, so, to establish a parameter or a morally solid limit to avoid the true execution of such program.